Client Good Moments: An Intensive Analysis of a Single Session - Stalikas, Anastassios; Fitzpatrick, Marilyn (Canadian Journal of Counselling and Psychotherapy, 2007)
An intensive analysis of a single counselling session conducted by Fritz Perls was carried out to examine relationships among client experiencing level, client strength of feeling, counselor interventions, and client good moments. Findings indicate that the occurrence of good moments is positively related to higher levels of experiencing and to higher levels of strength of feeling. Individual categories of counselor interventions were unrelated to good moments, experiencing, or strength of feeling. The possibility that positive therapeutic outcome is related to the accretion of good moments is discussed. Implications for counselling practice and research are reviewed.